Numerical investigation of the length of a polymer fuel cell on energy production in asymmetric flow and hydrogen production process - Mustafa, Jawed; Alqaed, Saeed; Sajadi, S. Mohammad; Aybar, Hikmet S. . (Elsevier, 2024)
In this study, a three-dimensional simulation of fuel cell (FUC) by using FEM is presented. The values of electrolyte potential (EPL), cell power (CPR), hydrogen mole fraction (HMF), water mole fraction (WMF), oxygen mole fraction (OMF), pressure, and rate changes in the channels are determined by changing the voltage from 0.1 to 0.8 V and the length of the hydrogen and oxygen channels (HOC) from 5 to 20 mm. This study is carried out by employing COMSOL software. The results reveal that an enhancement in the length of HOC reduces the amount of CPR. The maximum amount of CPR occurs when the HOC are 5 mm and the voltage is 0.5 V. The minimum amount of CPR corresponds to the channel length of 20 mm and a voltage of 0.8 V. At higher voltages, the use of longer channels increases the EPL. An increment in the voltage significantly reduces the EPL, while increasing the length of the HOC intensifies the EPL. An enhancement in the length of the channel and increasing the applied voltage results in a reduction in the HMF. An increase in the voltage results in a more significant reduction in HMF for larger lengths of the HOC.
Keywords: Fuel cell; Cell power; Potential electrolyte; Molar hydrogen content